Improvement of physico-mechanical and microstructural properties of magnesium phosphate cement composites comprising with Phosphogypsum. (10th July 2020) - Aminul Haque, M.; Chen, Bing; Liu, Yuantao; Farasat Ali Shah, Syed; Ahmad, Muhammad Riaz
Abstract: The current study aimed to utilize the Phosphogypsum (PG) as a mixing ingredient in the magnesium phosphate cement (MPC) matrix and the influence of PG on the physical, mechanical and microstructural properties were explored over the courses of age. For judging the well interactions between the PG and MPC, consecutive dosages such 10%–40%, 60% and 80% PG were introduced as the substitution of very fine aggregate. The analytical results revealed the progress of density and decline of inner void spaces of the solid specimens with the higher amounts of PG. Mechanical strength pointedly enriched for the inclusion of PG up to 40% and obtained the compressive strength and flexural strength more than 75 MPa and 12 MPa, respectively at 28d in air, which were above 90% of control samples. The mass losses were noticed around 2% at 28d curing age. Microstructural properties analyzed by scanning electron microscope (SEM) and X-ray diffraction (XRD) demonstrated the well formation of calcium silicate hydrate (CSH), ettringite and some intermediate minerals along with the main struvite crystal, which developed the structural integrity of matrices. The Fourier Transform Infrared spectroscopy (FTIR) analysis also confirmed the existence of new chemical groups in MPC with PG content that indicated the presence of CSH and ettringite. The outcomes of the current research can be a promising solution to reuse PG as an ingredient in the MPC compounds as well as reduce the environmental concern. Highlights: Different dosages of PG were added in MPC mortars as the replacement of MgO. PG improved the solidity and reduced the pores by forming intermediate crystals. MPC specimens with 10%–40% PG exhibited the well water resistant performance. SEM, XRD and FTIR observations ascertained the existence of CSH and Ettringite.